2020
DOI: 10.2174/1745017902016010125
|View full text |Cite
|
Sign up to set email alerts
|

Implementing WHO-Quality Rights Project in Tunisia: Results of an Intervention at Razi Hospital

Abstract: Background: The aims were: 1) to measure the attitudes of learners (and future trainers) before and after a course on WHO-Quality Rights (QR); 2) to evaluate a psychiatric ward, by previously trained staff on QR, comparing it with a previous evaluation and discussing an improvement plan. Methods: 1) Training sample: 19 subjects (8 males), 41.4±10.6 years, including jurists/lawyers, health professionals, and experts. The QR team developed the 26-item tool to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 7 publications
1
17
0
3
Order By: Relevance
“…However, there are large deviations between wards in terms of adopting alternatives. There is still room for further development in inpatient psychiatric services as the total mental health workforce is high in Finland, [ 17 ] and no scarcity of resources was found in our study, unlike in many other countries [ 8 , 11 ].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…However, there are large deviations between wards in terms of adopting alternatives. There is still room for further development in inpatient psychiatric services as the total mental health workforce is high in Finland, [ 17 ] and no scarcity of resources was found in our study, unlike in many other countries [ 8 , 11 ].…”
Section: Discussionmentioning
confidence: 62%
“…The Tool Kit is designed for use in LMIC and high-income countries, as it is an essential resource, not only for putting an end to past neglect and abuses but also for ensuring high-quality services in the future [ 5 ]. To date, the Tool Kit has been used for reviewing mental health facilities in many areas around the world, [ 6 ] including Egypt, [ 7 ] Tunisia, [ 8 ] Greece, [ 10 ] the Czech Republic, [ 11 ] Chile, [ 12 , 13 ] and India. [ 14 ] These reports reveal a variety of deficits in mental health services, both in LMIC and in high-income countries, beginning with the poor physical state of the hospitals, [ 11 ] service users not being able to live independently in society, [ 9 , 13 ] and a lack of preventive measures to avoid maltreatment and cruelty [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are examples of training interventions which have succeeded in decreasing stigma among health professionals (Villani and Kovess-Masfety, 2017). A training course on the CRPD and the QualityRights toolkit was organized in Elrazi after this study and showed significant differences in the awareness of rights by the participants before and after the one-week course (Carta et al , 2020). It is important to underline, however, that even though training the staff, the service users and their families on human rights is necessary, it is not enough to change the situation.…”
Section: Discussionmentioning
confidence: 98%
“…Este é o tipo mais amplo de métodos de revisão de pesquisa, permitindo a inclusão simultânea de pesquisas experimentais e não experimentais, a fim de entender melhor um fenômeno preocupante (WHITTEMORE;KNAFL, 2005). Esta revisão passou pelas seguintes etapas, adaptadas do modelo de Whittemore e Knafl ( 2005 (BRASIL, 2015;CARTA et al, 2020).…”
Section: Objetivos Específicosunclassified